2022
DOI: 10.1155/2022/8002963
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Forensic Readiness Framework Applicable to the Drone Forensics Field

Abstract: The Drone Forensics (DRFs) field is a branch of digital forensics, which involves the identification, capture, preservation, reconstruction, analysis, and documentation of drone incidents. Several models have been proposed in the literature for the DRF field, which generally discusses DRF from a reactive forensic perspective; however, the proactive forensic perspective is missing. Therefore, this paper proposes a novel forensic readiness framework called Drone Forensics Readiness Framework (DRFRF) using the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Recently, many researchers have introduced their work in the DRFI field. These include, (Alotaibi et al, 2022b), the authors introduced a new framework for drone forensic readiness. They address several issues in the DRFI field, despite the fact that their framework hasn't been put into practice (Al-Dhaqm et al, 2021a;Alotaibi et al, 2022b;Atkinson et al, 2021;Lan and Lee, 2022;Husnjak et al, 2022;Parghi et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, many researchers have introduced their work in the DRFI field. These include, (Alotaibi et al, 2022b), the authors introduced a new framework for drone forensic readiness. They address several issues in the DRFI field, despite the fact that their framework hasn't been put into practice (Al-Dhaqm et al, 2021a;Alotaibi et al, 2022b;Atkinson et al, 2021;Lan and Lee, 2022;Husnjak et al, 2022;Parghi et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Various studies have been reported that investigate and recognize cybercrime [22,[31][32][33][34][35][36][37][38][39][40], data cracks [23,[41][42][43][44][45][46][47][48][49][50], and other digital risks [24,25,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58].…”
Section: A Related Workmentioning
confidence: 99%
“…The Incident Response: This stage in DRFM is used to respond to drone incidents. A typical set of components in a drone system should identify when the drone is under attack from any devices like a system, laptop, mobile phone, router, radio controller, or other components [42,43]. These all devices or components have digital evidence related to drone investigation.…”
Section: Stage 1: Identification Stagementioning
confidence: 99%
“…Examining the Acquired Data: The data acquired and preserved in the previous stage should be examined to check and verify the authenticity of the data [42]. Examiner should rehash the hashed value of the received data and check the consistency of the data.…”
mentioning
confidence: 99%